2022
DOI: 10.1111/ijfs.15572
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the effects of vacuum frying on frying medium and fried foods properties

Abstract: Vacuum frying (VF) is a process developed at a pressure lower than atmospheric pressure, in which lower temperatures are employed to remove moisture from the food and reduce the oil content in the final product. Diverse studies have been published for VF or assisted with microwave and ultrasound, facing the challenges of accomplishing the physical and sensory properties appreciated in fried products. The studied matrices under VF include mainly vegetable origin foods (apple, banana, carrot, donuts, kiwi, mushr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…This result was confirmed by Lu et al, who found that there existed many nutrients, such as polysaccharides, soluble proteins, and soluble solids in the blanching water of P. eryngii ( 40 ). Furthermore, vacuum frying process resulted in increased oil content and loss of fat-soluble nutrients in samples ( 41 ). There were no significant differences in reducing sugar, protein and moisture contents of vacuum fried P. eryngii chips with different pretreatments.…”
Section: Resultsmentioning
confidence: 99%
“…This result was confirmed by Lu et al, who found that there existed many nutrients, such as polysaccharides, soluble proteins, and soluble solids in the blanching water of P. eryngii ( 40 ). Furthermore, vacuum frying process resulted in increased oil content and loss of fat-soluble nutrients in samples ( 41 ). There were no significant differences in reducing sugar, protein and moisture contents of vacuum fried P. eryngii chips with different pretreatments.…”
Section: Resultsmentioning
confidence: 99%
“…The vacuum frying (VF) technique was developed in the 1960s as an alternative to the conventional frying method (Sosa-Morales et al, 2022). VF fried food had reduced oil/fat content, improved nutritional profile, and decreased amount of oxidation products because the frying process was performed in almost vacuum at a low temperature (<95 • C).…”
Section: Ultrasonic-and Microwave-assisted Vacuum Fryingmentioning
confidence: 99%
“…Although the quality of vacuum frying products has improved considerably, it still falls short of consumer expectations. In response to the need for healthier fried foods with lower oil content and acceptable taste and quality, VF is being combined with other technologies, such as microwave and ultrasonic treatment 44,45 . Microwave technology, when used in conjunction with vacuum frying, not only greatly reduces the time‐consuming production process but also reduces the fat content 46,47 .…”
Section: New Processing Techniquesmentioning
confidence: 99%
“…In response to the need for healthier fried foods with lower oil content and acceptable taste and quality, VF is being combined with other technologies, such as microwave and ultrasonic treatment. 44,45 Microwave technology, when used in conjunction with vacuum frying, not only greatly reduces the time-consuming production process but also reduces the fat content. 46,47 The application of ultrasonic assisted drying in the vacuum frying process reduces drying time and energy consumption.…”
Section: Fryingmentioning
confidence: 99%